1993
DOI: 10.1128/jb.175.19.6179-6185.1993
|View full text |Cite
|
Sign up to set email alerts
|

Functional domains of S-type pyocins deduced from chimeric molecules

Abstract: Functional domain structures of pyocins AP41, Si, and S2 were assigned by examining the functions of chimeric pyocins and deletion derivatives. Pyocins AP41, S1, and S2 are essentially composed of three domains, the receptor-binding domain, the translocation domain, and the DNase domain, in that order from the N terminus to the C terminus. The alignment of these domains is distinct from that in E2-group colicins with functions similar to those of these pyocins. Pyocins AP41 and S2 have a fourth domain between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…Similarly, bacteriocins from distantly related species frequently share homologous cytotoxic domains but unrelated translocation and receptor binding domains. For example, colicin E9 and pyocin S2 share sequence homology within their C-terminal cytotoxic domains, but sequences of the translocation and receptor binding domains appear to be unrelated (17). A variation on this mechanism of bacteriocin evolution is illustrated by the recently described pectocins M1 and M2.…”
mentioning
confidence: 99%
“…Similarly, bacteriocins from distantly related species frequently share homologous cytotoxic domains but unrelated translocation and receptor binding domains. For example, colicin E9 and pyocin S2 share sequence homology within their C-terminal cytotoxic domains, but sequences of the translocation and receptor binding domains appear to be unrelated (17). A variation on this mechanism of bacteriocin evolution is illustrated by the recently described pectocins M1 and M2.…”
mentioning
confidence: 99%
“…Similar to the organization of colicins genes, the pyocin loci encode two protein components: a larger protein bearing the killing activity and a smaller protein conferring immunity towards the producing bacteria (Duport et al, 1995;Elfarash et al, 2012;Ling et al, 2010;Michel-Briand & Baysse, 2002;Sano & Kageyama, 1984;Sano et al, 1993). All S-type pyocins are composed of three or four domains.…”
Section: Introductionmentioning
confidence: 99%
“…The killing domain and the immunity region, form part of the remaining colicin protein which is a short sequence and takes part in immunity protein binding. Pyocins produced by Pseudomonas aeruginosa are also similar to colicin structure but the order of translocation and receptor recognition domains are switched (Sano et al, 1993).…”
Section: Bacteriocins Of Gram Negative Bacteriamentioning
confidence: 96%
“…Studies by Pugsley, (1984a) revealed that colicins have a mass of 29 to 90 KDa with receptors for specificity, translocation, or killing activity. Sano et al (1993) later found that pyocins secreted by P. aeruginosa have similar domain constructs. Bacteriocins produced by gram-positive bacteria appear supposed to have been formed initially as prepeptides and later separated from the main peptide to form the biologically active molecule.…”
Section: Protein Structure Of Bacteriocinsmentioning
confidence: 99%